2018
DOI: 10.1186/s12985-018-1066-8
|View full text |Cite
|
Sign up to set email alerts
|

Satisfactory virological response and fibrosis improvement of sofosbuvir-based regimens for Chinese patients with hepatitis C virus genotype 3 infection: results of a real-world cohort study

Abstract: BackgroundChronic hepatitis C virus (HCV) genotype (GT) 3 infection with advanced liver disease has emerged as a challenging to treat by direct-acting antivirals (DAAs), but the efficacy of DAAs in Chinese HCV-GT3 patients is rarely reported. This study aimed to analyze the efficacy of sofosbuvir (SOF)-based regimens in Chinese patients with HCV-GT3 and compensated liver disease.MethodsThis was a registered retrospective study. All patients had completed at least 12 weeks SOF-based regimens therapy (with or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 23 publications
3
17
1
Order By: Relevance
“…31 A real-world study from China rst reported that liver brosis evaluated by APRI and FIB-4 were signi cantly improved in patients with genotype 3 infection. 27 In present study, we also found that brosis improvement evaluated by APRI and FIB-4 occurred in most of patients, including patients with cirrhotic or high viral load but not patients with HBV co-infection, treatment experienced or normal level of ALT at baseline, which was diametrically opposed to that in above study has been mentioned. In our opinion, it's an issue of great concern to monitoring of cirrhotic status for patients with following characteristics, treatment experienced, HBV co-infection or normal level of ALT at baseline.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…31 A real-world study from China rst reported that liver brosis evaluated by APRI and FIB-4 were signi cantly improved in patients with genotype 3 infection. 27 In present study, we also found that brosis improvement evaluated by APRI and FIB-4 occurred in most of patients, including patients with cirrhotic or high viral load but not patients with HBV co-infection, treatment experienced or normal level of ALT at baseline, which was diametrically opposed to that in above study has been mentioned. In our opinion, it's an issue of great concern to monitoring of cirrhotic status for patients with following characteristics, treatment experienced, HBV co-infection or normal level of ALT at baseline.…”
Section: Discussioncontrasting
confidence: 45%
“…Neither sub-genotype information was provided nor the effect of ribavirin on SVR12 was analyzed. 27 Another real-world study from China showed that genotype 3a infected patients yield high and similar SVR12 rate in SOF/VEL and SOF + DCV ± RBV regimens. 28 However, the number of patients enrolled were small and the SVR12 rate on 3b sub-type with cirrhosis wasn't shown.…”
Section: Discussionmentioning
confidence: 98%
“…These findings have been confirmed in real-world cohort studies for both glecaprevir/ pibrentasvir (153,(165)(166)(167)(181)(182)(183) and sofosbuvir/ velpatasvir. (169,170,(184)(185)(186)(187)(188)(189) Based on these data, recommended regimens for adults eligible for the simplified treatment algorithm are 8 weeks of glecaprevir/pibrentasvir for patients with genotype 1-6 or 12 weeks of sofosbuvir/velpatasvir for those with genotype 1, 2, 4, 5, or 6. Pretreatment RAS testing is recommended for persons with genotype 3 because only those without a baseline NS5A Y93H RAS are eligible for a 12-week course of sofosbuvir/ velpatasvir.…”
Section: Simplified Hcv Treatment Algorithm For Treatment-naive Adultmentioning
confidence: 99%
“…Several real-world cohorts have evaluated SOF/VEL effectiveness and safety in varying settings, with the results being similar to those of clinical trials. 10,[15][16][17][18][19][20][21][22][23][24] In this integrated real-world analysis, data from 12 clinical practice cohorts across different real-world settings in Canada, Europe and the USA were pooled to allow the evaluation of the real-world effectiveness of SOF/VEL for 12 weeks without ribavirin (based on the label or physician discretion) in the largest available heterogeneous HCV patient population and to investigate any patient characteristics affecting the risk of not achieving SVR. (Table 1)…”
Section: Introductionmentioning
confidence: 99%